2015
DOI: 10.1039/c5tc00311c
|View full text |Cite
|
Sign up to set email alerts
|

Water effect on the spin-transition behavior of Fe(ii) 1,2,4-triazole 1D chains embedded in pores of MCM-41

Abstract: The spin-crossover (SCO) compounds [Fe(Htrz) 3 ](BF 4 ) 2 ÁH 2 O (SCO-1) and [Fe(Htrz) 2 trz]BF 4 (SCO-2) (Htrz = 1,2,4triazole) were embedded in the pores of mesostructured silica MCM-41 to yield SCO@MCM composites as evidenced by electron microscopy, gas sorption studies, powder X-ray diffractometry, atomic absorption and infrared spectrometry. Studies of the temperature-induced spin crossover behavior of the composites by temperature-variable 57 Fe Mössbauer spectroscopy, magnetic and differential scanning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 46 publications
(76 reference statements)
1
38
0
Order By: Relevance
“…59 CO 2 micropore analysis at 273 K versus N 2 analysis at 77 K ensures cardinally faster equilibration and hence analysis time as well as a slight extension of the range of analysis to pores of smaller sizes that are accessible to CO 2 molecules, but not to N 2 (~3.30 vs 3.64 Å 25 kinetic diameters respectively). 49,60 Higher temperature speeds up the equilibration considerably, 61 while the smaller kinetic diameter of CO 2 also improves somewhat the access to the micropores. CO 2 adsorption (Fig.…”
Section: Synthesis Analytics and Porosity Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…59 CO 2 micropore analysis at 273 K versus N 2 analysis at 77 K ensures cardinally faster equilibration and hence analysis time as well as a slight extension of the range of analysis to pores of smaller sizes that are accessible to CO 2 molecules, but not to N 2 (~3.30 vs 3.64 Å 25 kinetic diameters respectively). 49,60 Higher temperature speeds up the equilibration considerably, 61 while the smaller kinetic diameter of CO 2 also improves somewhat the access to the micropores. CO 2 adsorption (Fig.…”
Section: Synthesis Analytics and Porosity Characterizationmentioning
confidence: 99%
“…35 However, recently we have observed that in [Fe(Htrz) 3 ](BF 4 ) 2 ·H 2 O@MCM-41 (Htrz = 4H-1,2,4-triazole) and [Fe(Htrz) 2 trz]BF 4 @MCM-41 (trz = 1,2,4-triazolato), the mesoporous zeolite matrix loosely surrounds the embedded 1D SCO polymer and can still transfer the confinement pressure 40 through adsorbed water molecules as mediators, significantly altering the width of the hysteresis, the abruptness of the transition, and shift the latter to higher temperatures. 49 Guided by this finding we have chosen the micro-tomesoporous NH 2 -MIL-101(Al) metal-organic framework (MOF) 45 material as a stable, diamagnetic, optically transparent host, 50 for the placement of the charge-neutral mononuclear SCO complex [Fe(HB(pz) 3 ) 2 ], 1, targeting a new SCO composite material, S@M, based on a rigid porous matrix with aimed loose placement of the functional entities. 50 …”
Section: Introductionmentioning
confidence: 99%
“…However, the drying process has an additional effect as it shifts the transition to higher temperatures, that may be attributed to a positive pressure effect of the network densification on the nanocrystals. [57][58][59][60] This effect could also explain the higher transition temperature of the composite compared to the particle free system.…”
mentioning
confidence: 91%
“…has confined the Fe‐triazole complex ([Fe(Htrz) 3 ](BF 4 ) 2 ⋅ H 2 O (SCO‐1) and [Fe(Htrz) 2 trz](BF 4 ) (SCO‐2)) in silica MCM‐41 and observed large changes in the hysteresis width, depending on the water content and the solvent used during the nanoparticle synthesis (MeOH vs EtOH) . In SCO‐1@MCM, compared to bulk SCO‐1, the shift in temperature is significant, up to T ↑=371/376 K (neat SCO‐1, T ↑=282/291 K) and down to T ↓=340/345 K (neat SCO‐1, T ↓=276/286 K), where the symbols ↑ and ↓ indicate consecutive heating and cooling‐cycles, respectively …”
Section: Figurementioning
confidence: 99%